2021
DOI: 10.4103/aer.aer_58_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Local Infiltration Analgesia and Ultrasound Guided Single Shot Adductor Canal Block Post Total Knee Replacement Surgery - A Randomized Controlled Trial

Abstract: Context: Good quality analgesia posttotal knee arthroplasty (TKA) contributes majorly to early mobilization and shorter hospital stay. Aim: To compare adductor canal block (ACB) versus local infiltration analgesia (LIA) for postoperative pain relief in patients undergoing TKA. Settings and Design: This prospective, single-blind, randomized controlled trial was undertaken at a tertiary care university hospital. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…15 Recent studies have shown that they might not provide much pain relief compared with local PAI alone, but this study found that pain levels at 2 and 3 hours postoperatively were on average two points out of 10 less in those who had a preoperative single-shot ACB in addition to local PAI at the time of wound closure than those who did not. 13,14,25 However, this did not translate into a notable reduction in pain levels at discharge or total MME consumption, nor did it decrease the time to ambulation or discharge from the PACU. A recent study by Than et al found that an anesthesiologist-administered single-shot ACB costs $893; hence, SDD TJA pathways should carefully select the perioperative protocol to improve outcomes and provide the most cost-effective care.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…15 Recent studies have shown that they might not provide much pain relief compared with local PAI alone, but this study found that pain levels at 2 and 3 hours postoperatively were on average two points out of 10 less in those who had a preoperative single-shot ACB in addition to local PAI at the time of wound closure than those who did not. 13,14,25 However, this did not translate into a notable reduction in pain levels at discharge or total MME consumption, nor did it decrease the time to ambulation or discharge from the PACU. A recent study by Than et al found that an anesthesiologist-administered single-shot ACB costs $893; hence, SDD TJA pathways should carefully select the perioperative protocol to improve outcomes and provide the most cost-effective care.…”
Section: Discussionmentioning
confidence: 95%
“…The addition of a peripheral adductor canal nerve block (ACB) was shown to reduce pain and increase ambulation distance the first 2 days after inpatient TJA, 11,12 although because two recent randomized trials of TKA found no decrease in pain or morphine milligram equivalent (MME) consumption compared with local periarticular injection (PAI). 13,14 Understanding the effect of preoperative ACBs on ambulation is important given the rise of SDD pathways. 15,16…”
mentioning
confidence: 99%
See 1 more Smart Citation